Physicochemical Properties and Floral Sources of Honey Produced in Marsabit Forest Reserve, Northern Kenya. (30th June 2022) - Muhati, Godwin Leslie; Warui, Mary Wanjiru
Abstract : This study assessed the physicochemical properties and floral sources (botanical origin) of sixteen honey samples collected from beekeepers in five clusters surrounding the Marsabit Forest Reserve (MFR) in northern Kenya. Analysis of Variance (ANOVA) was used to determine the differences in physicochemical properties of honey, while relative frequencies of pollen types in each honey sample were calculated and expressed as percentages. The mean physicochemical parameter values were moisture, 18.09 ± 0.86%; total reducing sugars, 73.03 ± 1.00%; apparent sucrose, 2.43 ± 0.66%; acidity, 20.25 ± 0.86 meq/kg; hydroxymethylfurfural (HMF), 11.01 ± 5.39 mg/kg. All parameter values were within limits set in the East African Standard, Codex Alimentarius, and the European Union directive standards for honey. Pollen analysis showed a total of 108 pollen types representing 55 families and 97 genera. The highest represented family in the honey samples was Euphorbiaceae. The study recommends the further uptake of apiculture and the training and facilitation of honey producers, processors, and traders on quality assurance and certification of honey to make them competitive in the markets beyond the local level.